Histochemical and enzymatic differences in skeletal muscle from Svalbard reindeer during the summer and winter - Kiessling, K.-H.; Kiessling, A.; Nilssen, K.; Andersson, I.-L. (Rangifer, 1986)
Enzyme activities and fibre properties in four muscles from Svalbard reindeer, collected during the summer, have been compared with corresponding muscles during the winter. In two muscles, gluteobiceps and semimembranosus, oxidative capacity is higher in winter than in summer; in the other two muscles, semitendinosus and longissimus dorsi, there is no difference with time of the year. The capacity to oxidize fatty acids is low in winter compared with summer, especially in semitendinosus and longissimus. These changes are similar in both sexes. Histochemical studies of the three main fibre types, I (BetaR), HA (°cR) and IIB (aW), from the four muscles show that in male reindeers the muscle fibres are narrower at the end of the winter season than during the summer. The decrease of muscle tissue amounts to about one third of the total volume (33%), of which I accounts for 5%, IIA for 2% and IIB for 26%. The results indicate that the Svalbard reindeer use lean tissue in general, and IIB fibres in particular, in order to survive the hostile arctic winter period at Svalbard. Histokemiska och enzymatiska skillnader i skelettmuskel från Svalbardren mellan sommar och vinter. Abstract in Swedish / Sammandrag: Enzymaktiviteter och fiberegenskaper i fyra av Svalbardrenens muskler, insamlade under sommaren, har jåmforts med motsvarande muskler insamlade under vintern. I två muskler, gluteobiceps och semimembranosus, år oxidativa kapaciteten hogre under vintern an under sommaren; i de andra två musklerna, semitendinosus och longissimus dorsi, foreligger ingen skillnad i detta avseende. Kapaciteten att oxidera fettsyror år låg under vintern jåmfort med sommaren, speciellt i semitendinosus och longissimus. Inga konsskillnader foreligger i dessa avseenden. Histokemiska studier av de tre huvudtyperna av muskelfibrer, fiR (I), ocR (IIA) och (IIB), från de fyra musklerna visar att hos handjuren år fibrerna tunnare vid slutet av vintersåsongen jåmfort med sommaren. Denna minskning i muskelvåvnad uppgår till en tredjedel av totala volymen (33%). Harav svarar ftR for 5%, ^R tor 2% och for 26%. Resultaten antyder att Svalbardrenen anvånder muskelvåvnad, speciellt QcW fibrer, for att overleva undri den hårda arktiska vinterperioden på Svalbard.